Incidence, Risk Factors and Outcome of Neonatal Acute Kidney Injury: An Observational Study - Poudel, Daman R; Basnet, Srijana; Shrestha, Laxman P (Journal of Institute of Medicine Nepal, 2022)
Introduction: Acute kidney injury (AKI) is common in neonates admitted in neonatal intensive care unit (NICU) and is associated with high death rates and prolong hospital stay. We aimed to determine the incidence, risk factors and outcome of neonatal AKI in a single tertiary center in Nepal. Methods: This was a prospective observational study of all neonates admitted to NICU between January 2019 to December 2019. Those with AKI were further assessed for risk factors and outcomes. Neonates who survived or stayed less than 72 hours, evidence of congenital renal anomalies, or with incomplete data were excluded. Need of peritoneal dialysis, mortality and length of NICU stay were the outcomes studied among neonates with AKI. Logistic regression models were used for adjustment of covariates and risk analysis were expressed in terms of odds ratio with its 95% confidence interval. Results: The incidence of AKI was 37.5% (42/112 patients). Compared with neonates without AKI, those with AKI had a lower birth weight (2421±960 vs 1741±1142gram, p<0.001) and a lower gestational age (36.1±7.8 vs. 32.4±3.9 weeks, p<0.001). Sepsis (OR, 4.5; 95% CI, 0.7–30) and nephrotoxic drug exposure (OR, 4; 95% CI, 1.4–7) were significantly associated with increased AKI risk. Mortality was 40% (17/42) among neonates with AKI and 3% (2/70) among those without AKI (p<0.001). Conclusion: Over one-third of neonates in NICU developed AKI. Prematurity, low birth weight, sepsis and nephrotoxic drug exposure were risk factors for Neonatal AKI. Mortality was almost 50% in neonatal AKI.